Investigation into the optimal fleet employment strategy with concentration on the supramax bulk carrier east of Suez market - Rusli, Adelina Astra (2014)
In this research we investigate the optimal fleet employment strategy by looking at the 646,646 permutations derived from 13 different combinations of acquisition-employment strategy for a portfolio of 10 Supramax vessels for the period 2006 to 2012.